Real cowboys - Hoefler, Kate (Houghton Mifflin Harcourt, 2016)
Cowboys are strong and tough. Cowboys ride fast horses and travel far and wide. But as they move through canyons and across prairies, quietly doing their work, cowboys are many more things, too. And these are the things that make them real cowboys.